James Green ('De Libra') and "Sydney Architecture Aesthetically Considered". Issue 3 (2nd September 2018) - Hogben, Paul
ABSTRACT: Among the various voices in the ferment of architectural discourse in late nineteenth-century Australia that of James Green is perhaps one of the least understood. This, despite the fact he was a prolific writer, edited one of Australia's most widely circulated building journals and was a prominent commentator on modern American architecture. This paper sheds light on the contribution Green made to architectural discourse in Australia by focussing on two of his most significant interests, that of the architecture of Sydney and the so-called "American Romanesque". The paper argues that Green's critical evaluation of these subjects holds the key to understanding his theoretical and intellectual position on modern city architecture. Specifically, it was Green's nine-part series entitled "Sydney Architecture Aesthetically Considered" published in the Australasian Builder and Contractors' News in 1890 in which he articulated the principles he thought should guide the elevational composition and treatment of city buildings. As the paper shows, this series served as a platform enabling Green to exercise a critical voice on other architectural matters, including the topic of American Romanesque architecture and its influence in Australia.